A SCIENTOMETRIC ANALYSIS OF IETE JOURNAL OF RESEARCH (1998 – 2008) - Kadbe, Mahesh M.; Borkar, Dr. Vikas S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looks at the IETE Journal of Research’s research output between 1998 to 2008. The research utilized information from the Web of Science database. The primary aim of the study is to evaluate the scientific contributions of the article under consideration. The analysis includes the number of articles, the distribution of articles by year, the authorship pattern that provide the largest contributions to the journal. The analysis found that over the study period, a total of 591 research papers were published in the journal. The study’s findings were visually displayed using the VOSviewer tool.